Steinbeck in the Ukraine - unknown:::Creator::::::::::::
John and Elaine Steinbeck with Frida Lurie (Russian interpreter), and Peter Bridges, who sits, (US embassy officer and Steinbeck's interpreter, who made sure Lurie gave accurate interpretations).